THE EFFECT OF FINANCIAL PERFORMANCE ON STOCK RETURNS OF ISLAMIC BANKS WITH INFLATION AS A CONTROL VARIABLE - Buchori, Imam; Elina, Riskiana; Hidayat, Moh. Helmi (NISBAH: Jurnal Perbankan Syariah, 2025)
This research seeks to analyze the influence of Return on Equity (ROE), Price to Earnings Ratio (PER), and Financing to Deposit Ratio (FDR) on the stock returns of Islamic banks, with inflation incorporated as a control variable. The study adopts a quantitative explanatory approach, aiming to empirically test the relationships between the formulated variables based on theoretical hypotheses. The data employed in this research consists of quarterly financial statements from Islamic commercial banks that are publicly listed on the Indonesia Stock Exchange (IDX), spanning a period of three quarters. Data collection was carried out through non-participant observation, ensuring objectivity without researcher intervention. For data analysis, the study utilizes panel data regression techniques, allowing for the simultaneous evaluation of time-series and cross-sectional data. The findings reveal that inflation, as a control variable, enhances the explanatory power of financial performance indicators in predicting stock returns. Additionally, the study confirms that ROE, PER, and FDR each exert a significant impact on the stock returns of Islamic banks.